Fabrication of Self‐Cleaning CNT‐Based Near‐Perfect Solar Absorber Coating for Non‐Evacuated Concentrated Solar Power Applications. Issue 12 (19th October 2020) - Bera, Raj Kumar; Binyamin, Yaniv; Frantz, Cathy; Uhlig, Ralf; Magdassi, Shlomo; Mandler, Daniel
Abstract : A near‐perfect black solar absorber made of carbon nanotubes (CNTs) prepared by a low‐cost wet‐deposition method on a reflective metal surface for mid‐temperature non‐evacuated concentrated solar power (CSP) applications is demonstrated. The dispersed CNTs in an alumina–silica matrix exhibit an absorptance of 0.985 in the entire solar spectrum and emittance of 0.90 in the infrared (IR) region. The coating shows high durability and is super‐hydrophilic (0° contact angle) after plasma treatment, without affecting the solar absorptance and excellent coating adhesion. The efficiency of the coating is evaluated by analytical models, which implies that it has higher efficiency at low temperature and at a high solar concentration ratio than that of previously reported selective coatings. Abstract : A self‐cleaning near‐perfect solar absorber based on caarbon nanotube–based black coating is fabricated for mid‐temperature solar‐thermal applications. The coating exhibits a high absorptance of 0.985 in the entire solar spectrum and durable super‐hydrophilic property with 0° water contact angle.